Leveraging AI in academia: university students’ adoption of ChatGPT for writing coursework (take home) assignments through the lens of UTAUT2 - Namatovu, Afulah; Kyambade, Mahadih (Taylor & Francis Ltd, 2025)
The rapid growth of artificial intelligence (AI) is transforming education, with tools like ChatGPT offering innovative support for university students in tasks such as essay writing and problem-solving. This study examines factors influencing ChatGPT adoption among students in Uganda, using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework. The UTAUT2 model explores performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit as key drivers of technology use. A mixed-method approach was employed, involving a survey of 473 third-year Makerere University Business School students and qualitative interviews. Structural equation modeling (SEM) analyzed relationships between UTAUT2 constructs and students’ intentions to use ChatGPT. The findings show that performance expectancy, habit, and social influence significantly impact adoption, while effort expectancy and price value have less influence. This research highlights the potential of AI to enhance academic performance in resource-constrained settings. The insights are valuable for educators and policymakers aiming to integrate AI tools effectively in developing countries, addressing barriers like limited digital literacy and technological access. The study provides a foundation for strategies that support the adoption of AI in higher education, enhancing learning outcomes in Uganda’s unique socio-economic context.